Extracorporeal Shockwave Lithotripsy for Ureteral Stones: Twelve years of Experience with 2836 Patients at a Single Center - Demirbas, Murat; Samli, Murat; Karalar, Mustafa; Kose, Ahmet C. (Urology Journal, 2012)
PURPOSE: To retrospectively analyze the efficacy of extracorporeal shockwave lithotripsy (SWL) for managing ureteral stones in patients who were treated during a 12-year period at a single center in Turkey. MATERIALS AND METHODS: The study involved 3300 patients who had single ureteral stone and underwent SWL between January 1999 and March 2011. Medical records from 2836 (85%) patients were available for evaluation. Only patients with radiopaque stones of 5- to 15-mm diameter were included. All procedures were carried out by an experienced urologist (ACK). Patients with proximal ureteral calculi were treated in supine position. Those with mid or distal ureteral stones were treated in modified prone position. Persistence of radiologic image of the stone after three SWL sessions or no spontaneous passage of stone fragments after one month of follow-up was defined as treatment failure. Treatment success was defined as radiologically confirmed fragmentation and spontaneous passage of the stone. RESULTS: The success rates for the subgroups with stones located in the proximal, mid, and distal ureter were 85.1%, 83.9%, and 88.4%, respectively (P = .257). The success rates for individuals with smaller stones (≤ 10 mm) in the proximal, mid, and distal ureter were 90%, 85.8%, and 90.4%, respectively (P = .07). The corresponding rates for individuals with larger stones (> 10 mm) were 75.3%, 81.3%, and 81.6%, respectively (P = .09). CONCLUSION: Our retrospective evaluation of this large patient series reveals that SWL is effective for treating stones in the proximal, mid, and distal ureter.